Investigating the widely held belief that men and women with learning disabilities receive poor quality healthcare when admitted to hospital: a single‐site study of 30‐day readmission rates. (31st March 2015) - Kelly, C. L.; Thomson, K.; Wagner, A. P.; Waters, J. P.; Thompson, A.; Jones, S.; Holland, A. J.; Redley, M.
Abstract Background This study aims to use 30‐day readmission rates to investigate the presumption that men and women with learning disabilities (LDs, known internationally as intellectual disabilities) receive poorer quality hospital care than their non‐disabled peers. Method A 12‐month retrospective audit was conducted using Hospital Episode Statistics (HES) at a single acute hospital in the East of England. This identified all in‐patient admissions; admissions where the person concerned was recognised as having a LD; and all emergency readmissions within 30 days of discharge. Additionally, the healthcare records of all patients identified as having a LD and readmitted within 30 days as a medical emergency were examined in order to determine whether or not these readmissions were potentially preventable. Results Over the study period, a total of 66 870 adults were admitted as in‐patients, among whom 7408 were readmitted as medical emergencies within 30 days of discharge: a readmission rate of 11%. Of these 66 870 patients, 256 were identified as having a LD, with 32 of them experiencing at least one emergency readmission within 30 days: a readmission rate of 13%. When examined, the healthcare records pertaining to these 32 patients who had a total of 39 unique 30‐day readmissions revealed that 69% (n = 26) of these readmissions were potentially preventable. Conclusion Although overall readmission rates were similar for patients with LDs and those from the general population, patients with LDs had a much higher rate of potentially preventable readmissions when compared to a general population estimate from van Walraven et al. This suggests that there is still work to be done to ensure that this patient population receives hospital care that is both safe and of high quality.